Compact UWB MIMO antenna with pattern diversity and band rejection characteristics. Issue 6 (30th March 2017) - Ibrahim, Ahmed A.; Machac, Jan; Shubair, Raed M.
ABSTRACT: This article presents a compact size asymmetric CPW strip‐fed UWB two‐element MIMO antenna, with notched‐band behavior. The single‐antenna element of the MIMO configuration is composed of a semi‐elliptical patch radiator with asymmetric ground plane. The notched‐band behavior of the proposed antenna is achieved by inserting a simple folded stub to the patch radiator. This stub achieves the desired single stop‐band from 3.3 to 3.9 GHz for WIMAX. The two‐antenna elements are placed orthogonally to achieve pattern diversity which leads to an improved MIMO system performance and enhances the isolation between elements without using any decoupling structures. The antenna has dimensions of 50 × 28 mm 2 . The edge‐to‐edge distance between antenna elements is 0.15λ0 at 3 GHz. The proposed antenna is designed, simulated, fabricated, and tested. Results show that the two‐antenna elements operate at frequencies ranging from 2.8 to 11.5 GHz with return loss lower than −10 dB and insertion loss lower than −18 dB. The performance of the MIMO antenna diversity characteristics were verified through the calculation of the standard parameters and show the antenna suitability for MIMO systems. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1460–1464, 2017